Out-Of-Pocket Expenditure Associated with Physical Inactivity, Excessive Weight, and Obesity in China: Quantile Regression Approach - Zhao, Yang; He, Li; Marthias, Tiara; Ishida, Marie; Anindya, Kanya; Desloge, Allissa; D'Souza, Monique; Cao, Gaofang; Lee, John Tayu (S. Karger AG, 2022)
Introduction: Previous studies exploring associations of physical inactivity, obesity, and out-of-pocket expenditure (OOPE) mainly used traditional linear regression, and little is known about the effect of both physical inactivity and obesity on OOPE across the percentile distribution. This study aims to assess the effects of physical inactivity and obesity on OOPE in China using a quantile regression approach. Methods: Study participants included 10,687 respondents aged 45 years and older from the recent wave of the China Health and Retirement Longitudinal Study in 2015. Linear regression and quantile regression models were used to examine the association of physical activity, body weight with annual OOPE. Results: Overall, the proportion of overweight and obesity was 33.2% and 5.8%, respectively. The proportion of individuals performing high-level, moderate-level, and low-level physical activity was 55.2%, 12.7%, and 32.1%, respectively. The effects of low-level physical activity on annual OOPE were small at the bottom quantiles but more pronounced at higher quantiles. Respondents with low-level activity had an increased annual OOPE of 26.9 USD, 150.3 USD, and 1,534.4 USD, at the 10th, 50th, and 90th percentiles, respectively, compared with those with high-level activity. The effects of overweight and obesity on OOPE were also small at the bottom quantiles but more pronounced at higher quantiles. Conclusion: Interventions that improve the lifestyles and unhealthy behaviors among people with obesity and physical inactivity are likely to yield substantial financial gains for the individual and health systems in China.